Isolation and identification of beneficial orchid mycorrhizal fungi in Paphiopedilum barbigerum (Orchidaceae). (31st December 2022) - Tian, Fan; Liao, Xiao-Feng; Wang, Lian-Hui; Bai, Xin-Xiang; Yang, Yan-Bin; Luo, Zai-Qi; Yan, Feng-Xia
ABSTRACT: Seed germination and seedling development in nearly all orchid species rely on a symbiotic relationship with mycorrhizal fungi; however, this is not the case with all mycorrhizal fungi. This study aims to provide an understanding about the important role of mycorrhiza in seed germination and growth of Paphiopedilum barbigerum . Therefore, we isolated and identified endophytic fungi from the roots of wild P. barbigerum . The beneficial mycorrhizal fungi Epulorhiza sp. FQXY019 and Tulasnella calospora FQXY017 were screened by seed symbiotic germination tests and found to promote seed germination. However, only the seeds inoculated with FQXY019 progressed from the seed germination to rooting stage. This shows that mycorrhizal fungi and P. barbigerum have a specific relation at different growth phases. In addition, we selected FQXY019 and inoculated it into MS medium, B5 medium, OMA medium, and PDA medium. The results showed that FQXY019 co-cultured on PDA significantly promoted the increase in seedling fresh weight, leaf length, and root length ( p < .01). Furthermore, it significantly promoted the root number and leaf number of seedlings compared with those co-cultured on MS, B5, and OMA media and control ( p < .05). Thus, this study demonstrated the promoting effect of Epulorhiza sp. FQXY019 on seed germination and seedling development, making it an alternative method for the artificial propagation of P. barbigerum.